1999
DOI: 10.1037/0096-1523.25.6.1867
|View full text |Cite
|
Sign up to set email alerts
|

Children's haptic and cross-modal recognition with familiar and unfamiliar objects.

Abstract: Five-year-old children explored multidimensional objects either haptically or visually and then were tested for recognition with target and distractor items in either the same or the alternative modality. In Experiments 1 and 2, haptic, visual, and cross-modal recognition were all nearly perfect with familiar objects; haptic and visual recognition were also excellent with unfamiliar objects, but cross-modal recognition was less accurate. In Experiment 3, cross-modal recognition was also less accurate than with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
85
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 33 publications
6
85
3
Order By: Relevance
“…Easton et al (1997) found a marginally significant within-modality priming advantage in visual and haptic naming tasks, although there was no main effect of study modality on performance in either test modality. Bushnell and Baxt (1999) also found evidence for modality-specific representations, but used an old-new recognition task and thus provided no measure of priming. Furthermore, their study only assessed recognition by young children, who may display different recognition performance than adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Easton et al (1997) found a marginally significant within-modality priming advantage in visual and haptic naming tasks, although there was no main effect of study modality on performance in either test modality. Bushnell and Baxt (1999) also found evidence for modality-specific representations, but used an old-new recognition task and thus provided no measure of priming. Furthermore, their study only assessed recognition by young children, who may display different recognition performance than adults.…”
Section: Discussionmentioning
confidence: 99%
“…Haptic object recognition was long considered a poor relative of visual object recognition, since people's ability to recognize 2-D raisedline depictions of common objects by touch alone is quite poor (Lederman, Klatzky, Chataway, & Summers, 1990;Loomis, Klatzky, & Lederman, 1991). However, recognition of real, familiar objects by touch is both fast and accurate (Klatzky, Lederman, & Metzger, 1985), and there is excellent cross-modal priming for familiar objects (Bushnell & Baxt, 1999;. Transfer between vision and haptics is easily accomplished, indicating substantial representational similarities between the two modalities.…”
mentioning
confidence: 99%
“…Two conditions were included:vision as the input modality with haptic matching (V-H) and haptics as the input modality with visual matching (H-V). Given that both infants (e.g., Meltzoff & Borton, 1979) and children (e.g., Bushnell & Baxt, 1999) can successfully perform intermodal matching, we predicted that adult participants would be able to accurately identify the standard faces with above-chance accuracy. However, on the basis of Jones' (1981) findings, we expected that the H-V condition would result in poorer matching accuracy than the V-H condition.He argued that when touch is the input modality, cross-modal tasks tend to result in poorer performance than when vision is the input modality, owing to insufficient haptic processing.…”
Section: Methodsmentioning
confidence: 99%
“…Further, it has been established in the literature (Newell, Bülthoff & Ernst, 2003) that learning happens through a synthesis of modalities, rather than strictly through visual pathways. Thus, combining haptic and visual modalities may increase discrimination and possibly understanding: by navigating the virtual space of science disciplines and geospatial representations through manipulating tactile object and visualization, greater comprehension might result (Bushnell & Baxt, 1999). Children quite naturally try to make correlations so developing the maps into a matching activity might help students make and question correlations (American Association for the Advancement of Science, 1993;Gopnik & Astington, 1988).…”
Section: Hands-on Science Maps For Kidsmentioning
confidence: 99%